Kampanye Public Relations dalam Sosialisasi Program Mobil Aspirasi Kampung Juara (MASKARA) - Avrianti, Lerian (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
This study aims to find out in depth regarding the process of public relations campaign activities carried out by the West Java Province Village Community Empowerment Service in the socialization of the Kampung Champion Aspiration Car (Maskara) program. This study aims to identify problem identification, management, and evaluation of the Mascara program's public relations campaign at DPM Desa, West Java Province. This study uses the campaign model from Leon Ostergaard which has three stages starting from problem identification, management which includes planning and implementation and the evaluation stage. The method used in this research is descriptive qualitative method with data collection techniques in the form of in-depth interviews, observation, and documentation. The results of the study concluded that the Village DPM of West Java Province carried out campaign activities through several stages. First, the problem identification stage for DPM Village in West Java Province found facts and data that the Mascara program was created to realize the vision and mission of the West Java Government for the 2018-2023 period and to follow up on development and mobility issues in West Java. Second, at the management stage, the DPM Village of West Java Province determines planning starting from objectives, target publics, messages, actors to media that will be used during campaign implementation, then the implementation of campaign activities that are carried out directly and indirectly. Third, at the evaluation stage, DPM Desa West Java Province conducted monitoring based on data obtained by looking at the development of village strata in West Java and the evaluation process used the sampling method with evaluations in Mascara recipient villages.